PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, GOOD GOVERNANCE DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA METRO) - Alya Citra Utomo; Suyanto Suyanto; Kuncoro Budi Riyanto (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine the effect of the application of government accounting standards, good governance and human resource competence on the quality of financial reports at the Regional Financial and Asset Management Agency of Metro City. Data obtained from observations, documentation and questionnaires. The analysis technique used is data requirements analysis, and hypothesis analysis. The results of this study indicate that Human Resource Competence, Implementation of Government Accounting Standards, Good Governance affect the Quality of Metro City Government Financial Reports. Keywords: Government Accounting Standards, Good Governance, Human Resources Competence, Financial Reporting Quality.